Impaired Hippocampal Neurovascular Coupling in a Mouse Model of Alzheimer’s Disease - Li, Lin; Tong, Xin-Kang; Hosseini Kahnouei, Mohammadamin; Vallerand, Diane; Hamel, Edith; Girouard, Hélène (Frontiers in Physiology, 2021)
Alzheimer's disease (AD), the most common form of dementia, is characterized by neuronal degeneration and cerebrovascular dysfunction. Increasing evidence indicates that cerebrovascular dysfunction maybe a key or an aggravating pathogenic factor in AD. This emphasizes the importance to investigate the tight coupling between neuronal activity and cerebral blood flow (CBF) termed neurovascular coupling (NVC). NVC depends on all cell types of the neurovascular unit within which astrocytes are important players in the progression of AD. Hence, the objective of this study was to characterize the hippocampal NVC (NVC) in a mouse model of AD. Hippocampal NVC was studied in 6-month-old amyloid-beta precursor protein (APP) transgenic mice and their corresponding wild-type littermates using in vivo laser Doppler flowmetry to measure CBF in area CA1 of the hippocampus in response to Schaffer collaterals stimulation. Ex vivo two-photon microscopy experiments were performed to determine astrocytic Ca2+ and vascular responses to electrical field stimulation (EFS) or caged Ca2+ photolysis in hippocampal slices. Neuronal synaptic transmission, astrocytic endfeet Ca2+ in correlation with reactive oxygen species (ROS), and vascular reactivity in the presence or absence of Tempol, a mimetic of superoxide dismutase, were further investigated using electrophysiological, caged Ca2+ photolysis or pharmacological approaches. Whisker stimulation evoked-CBF increases and ex vivo vascular responses to EFS were impaired in APP mice compared with their age-matched controls. APP mice were also characterized by decreased basal synaptic transmission, a shorter astrocytic Ca2+ increase, and altered vascular response to elevated perivascular K+. However, long-term potentiation, astrocytic Ca2+ amplitude in response to EFS, together with vascular responses to nitric oxide remained unchanged. Importantly, we found a significantly increased Ca2+ uncaging-induced ROS production in APP mice. Tempol prevented the vascular response impairment while normalizing astrocytic Ca2+ in APP mice . These findings suggest that NVC is altered at many levels in APP mice, at least in part through oxidative stress. This points out that therapies against AD should include an antioxidative component to protect the neurovascular unit.